Russell Sbriglia and Slavoj Žižek, editors. Subject Lessons: Hegel, Lacan, and the Future of Materialism. Northwestern UP, 2020. - Vanessa Loh (Studies in 20th & 21st Century Literature, 2021)
Review of Russell Sbriglia and Slavoj Žižek, editors. Subject Lessons: Hegel, Lacan, and the Future of Materialism. Northwestern UP, 2020. 270 pp.
Keywords: materialism; consciousness; unconscious; dualism/non-dualism; Hegel; Lacan